Komunistinių leidinių, išėjusių buržuazijos valdymo metais Lietuvoje, bibliografavimo klausimai - Zaveckienė, Žiedūnė (Knygotyra, 1974)
The Institute of History of the Communist Party together with the Book Chamber of Soviet Lithuania are busy in bibliographying Communist publications, as a separate part of a national bibliography. Nowadays one gets into difficulties in bibliographying underground Communist publications, as many of them have completely disappeared. It will take much time the bibliography to be compiled and published. One who gets in touch with the history of revolutionary publishing, has to search for facts in a lot of sources. In the article one can find a detailed analysis of the most valuable bibliographic sources, created in 1920–1940, such as „Cathaloque of the Lithuanian workers Press Union“ (Tilže, 1930), the „Library of Communist Selftraining“, compiled by Zigmas Angarietis. In the Archives of the Institute of History of the Communist Party of Soviet Lithuania there is a list of separate publications of the Comissariat for Lithuanian affairs, of the Central Committee of the CP of Lithuania, of the directing organs of the Komsomol and other organisations (284 items). The bibliographic lists published in Communist publications are mentioned as well. The registring of Communist publications in official bibliographic indices of the bourgeoise Lithuania is mentioned separately. Though there wasn’t any systemathic registration of Communist publications, but on individual initiative of separate bibliographers the registring of legally issued Communist publications was carried on not only in Lithuania but abroad as well.